Інноваційні підходи до сегментації споживачів в епоху цифровізації: методи, інструменти та напрями застосування - Чернобровкіна, Світлана Віталіївна; Мірошник, Марія Володимирівна; Чернобровкін, А. В. (My University, 2025)
Обґрунтовано актуальність дослідження впливу цифровізації на результативність маркетингової діяльності підприємств в період повоєнного відновлення економіки України. Систематизовано проблеми підприємств при цифровізації управління маркетинговою діяльністю та проведено їх логіко-змістовне моделювання з метою визначення причинно-наслідкових зв’язків між ними. Визначено, що ключовою проблемою підприємства при цифровізації управління маркетинговою діяльністю є нестача кваліфікованих маркетологів. Показано основні групи забезпечення бізнес-процесів в сфері маркетингу та визначено перелік інструментів для кожної з них. Розроблено рекомендації щодо удосконалення забезпечення процесу управління маркетинговою діяльністю підприємства при відбудові економіки України, зокрема нормативно-правового, інформаційного, організаційного, матеріально технічного та фінансового. Систематизовано основні закони, які регулюють сферу цифровізації бізнесу, в тому числі, і маркетингову діяльність. Наведені можливі застосунки, які доцільно впроваджувати в управлінські процеси сфери маркетингу.

The relevance of the study of the impact of digitalization on the effectiveness of marketing activities of enterprises during the period of post-war recovery of the economy of Ukraine is substantiated. The purpose of the article is to determine the priority directions of digitization of marketing management, taking into account the challenges faced by the enterprise during the post-war reconstruction of the economy. The problems of enterprises in the digitalization of marketing activity management were systematized and their logical and meaningful modeling was carried out in order to determine the cause-and-effect relationships between them. It was determined that the key problem of the enterprise in the digitalization of marketing management is the lack of qualified marketers. The insufficient level of structuring of marketing management processes at the enterprise is a consequence of the lack of qualified marketers, the absence of a marketing management digitalization strategy and a low level of planning of marketing activities. The lack of qualified marketers is the reason for the lack of a digital marketing management strategy. The main groups of ensuring business processes in the field of marketing are shown and a list of tools for each of them is defined. Recommendations have been developed to improve the process of managing the marketing activities of the enterprise during the reconstruction of the economy of Ukraine, in particular regulatory, informational, organizational, material, technical and financial. The main laws that regulate the field of digitalization of business, including marketing activities, have been systematized. Possible applications that should be introduced into management processes in the field of marketing are given. In conditions of increased riskiness of the external environment, weakening of the internal environment due to the war, the effectiveness of the marketing activities of the enterprise can be ensured due to the digitalization of management processes in the field of marketing.
Innovative approaches to consumer segmentation in the digitalization era: methods, tools, and application directions
Keywords: цифровізація; бізнес-процеси; стратегія цифровізації; рентабельність; задоволеність споживачів; інструменти цифровізації; логіко-змістовне моделювання; digitalization; business processes; digitalization strategy; profitability; customer satisfaction; digitalization tools; logical and meaningful modeling